Billy Whiteman's daughters and Marjorie Suttiliff England
the two girls on the right and left are the daughters of Billy Whiteman and the girl in the middle is Marjorie Suttiliff England
Black and White photographs
Master list item #: 44
File location is in the Raton file Cabinet
Keywords: Whiteman, Billy; England, Marjorie Suttiliff; Female Photographs; Family Photographs; Outdoor Photographs; Cimarron, New Mexico